(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Hemodialysis (HD) patients are considered as a high-risk population for cardiovascular disease, within which morbidity and mortality have been determined to be associated with dyslipidemia, pro-inflammatory cytokines, increased levels of C-reactive protein (CRP), and adhesion molecules (ICAM-1, VCAM-1). Different markers have been investigated to detect inflammation in hemodialysis patients, as well as the prognostic values of these markers. Methods. The present study aimed to investigate the effect of nano-curcumin (120 mg) over 12 weeks on hs-CRP levels, adhesion molecules (ICAM-1, VCAM-1), and serum lipid profiles on hemodialysis patients in a randomized controlled clinical trial. Results. The results revealed that the mean serum hs-CRP level in the nano-curcumin group exhibited a decrease by the end of the study, when compared to mean serum hs-CRP level in the placebo group. However, this intra-group trend was not found to be statistically significant (P > .05). Nevertheless, a significant difference was determined between the values in the group receiving nano-curcumin, in comparison with the placebo group, at the end of the study (P < .001). Based on the attained results, mean serum levels of VCAM-1 in the nano-curcumin group were significantly reduced at the end of the study, compared with the placebo group (P < .001). Furthermore, the intra-group changes comparison showed significant reductions in serum levels of ICAM- 1 in patients treated with nano-curcumin at the end of the study (P < .05). Additionally, though decreases in mean triglycerides, total cholesterol, LDL-C were noted, there were no statistically significant intra-group differences (P > .05). Moreover, intra-group changes comparison of HDL-C levels and fasting blood sugar did not show any significant changes. Conclusion. The current study indicates that nano-curcumin may show beneficial effects in lowering inflammation and hs-CRP levels, as well as adhesion molecules (ICAM-1, VCAM-1), in hemodialysis patients. However, the evidence is still insufficient.